Learning metods of coletive sports and the construction of perceptions about the soccer (Impetus, 2021)
Introduction: The teaching method used by the teacher is of utmost importance for the development of the initiation of team sports. Therefore, the professional must find pedagogical actions through alternative practices to produce knowledge of the sport. Objective: To understand and relate the characteristics of the methods used in collective sports schools and the construction of concepts related to sport by students. Methodology: This study is a descriptive field investigation, with qualitative and quantitative analysis. The data collection was carried out with the observation of five classes, following the criteria established in an observation sheet. After the observation, a questionnaire was given to the teacher to identify his knowledge of the methodology used, then another questionnaire was given to the students that sought to establish the knowledge related to the concept of sport and the preference between participating or winning. Results: It can be observed that, regardless of the method used, the student's conceptual perception related to sports was related to health and pleasure. Conclusion: In addition to the methodology, external factors also end up influencing the construction of the student's perception in relation to sport, to which these factors were not addressed in the present study.